Banking Policy and the Exchanges - Robinson, Joan (Review of Economic Studies, 1936)
Journal Article Banking Policy and the Exchanges Get access Joan Robinson Joan Robinson Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 3, Issue 3, June 1936, Pages 226–229, https://doi.org/10.2307/2967630 Published: 01 June 1936